2014
DOI: 10.3233/wor-141918
|View full text |Cite
|
Sign up to set email alerts
|

The application of participatory ergonomics in a healthcare setting in Hong Kong

Abstract: BACKGROUND: Work-related musculoskeletal disorders (WRMDs) are recognized as a major source of significant pain and disability in the healthcare sector. However, they are preventable if appropriate surveillance and intervention programs are implemented. OBJECTIVE: The purpose of this paper is to describe the holistic ergonomic approach that was used to address the multifactorial problems encountered by healthcare workers in their daily work. METHODS: Using participatory ergonomics, healthcare workers in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Previous studies have reported inconsistent results regarding to the PE effects on health outcomes including MSDs. A RCT study in Hong Kong reported a positive effect on reducing musculoskeletal disorders with PE interventions among healthcare workers 23 . Droeze et al reported a clear relation between ergonomic implementation of recommendations and a reduction in MSD, which there were 72% of the dentists reported a reduction or disappearance of the main complaint in dentists 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported inconsistent results regarding to the PE effects on health outcomes including MSDs. A RCT study in Hong Kong reported a positive effect on reducing musculoskeletal disorders with PE interventions among healthcare workers 23 . Droeze et al reported a clear relation between ergonomic implementation of recommendations and a reduction in MSD, which there were 72% of the dentists reported a reduction or disappearance of the main complaint in dentists 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In this cluster randomized controlled trial, we assessed the efficacy of a PE intervention on ergonomic risk exposure, musculoskeletal disorders, and work ability 23 Droeze et al reported a clear relation between ergonomic implementation of recommendations and a reduction in MSD, which there were 72% of the dentists reported a reduction or disappearance of the main complaint in dentists. 24 A systematic review summarized that there was partial to moderate evidence that PE interventions have a positive impact on musculoskeletal symptoms, reducing injuries and workers' compensation claims, and a reduction in lost days from work or sickness absence.…”
Section: Main Findingsmentioning
confidence: 99%
“…In the current study, nurses obtained relevant knowledge of WRMDs and their consequences through lectures, effectively improving the risk perception of WRMDs. Training and lectures effectively increase awareness of safety and self-protection [47] and promote healthy practices among nurses [39]. The WRMD Awareness Month as a cue factor strengthens the belief in safe work behavior through brochure distribution and knowledge and skills competition [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that health behavior training can effectively reduce the occurrence of WRMDs among nurses [50,51]. In the current study, we adopted ergonomics as the theoretical guide, combined with the work characteristics of ICU nurses, and guided nurses to take a scienti c posture to engage in clinical nursing work.…”
Section: Discussionmentioning
confidence: 99%